SOSIALISASI PENGENALAN PENYAKIT MENULAR TBC (TUBERCULOSIS) PADA MASYARAKAT LANSIA DI BLUD UPTD PUSKESMAS KANDAI - Solo, Dian Munasari; Fitrawan, La Ode Muhammad; Halik, Halik; Jabbar, Asriullah; Wulandari, Desri; Berlian, Bintang; Mulya, Rita Jaya; Eva, Nur; Rosnani, Rosnani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Tuberculosis (TB) is an infectious disease that can affect everyone, from infants, children, adolescents, to the elderly and causes morbidity and mortality in more than 1 million people each year. The disease is caused by a pathogenic bacterium called Mycobacterium tuberculosis. The purpose of the service at BLUD UPTD Puskesmas Kandai is to educate the elderly community to know the infectious disease TB (TB) and the factors that cause it. The method used in this activity is the lecture method. In providing educational information about the introduction of TB (tuberculosis) infectious diseases using material in the form of power point soft files, after which a discussion or question and answer session is held between the elderly community and the speaker. The result of this activity is that the community can understand and know the symptoms and how to prevent TB (tuberculosis) disease.